Avaliação da força sofrida pelos dentes com a ação de lábios e língua - Amanda Freitas Valentim (2012)
The correct tooth alignment is associated with several factors. Among them, the balance of forces exerted by the lips and tongue on the dentoalveolar structures stands out. Evaluation of the duration and intensity of these forces as well as the location where they are applied is routinely carried out in a subjective way, leading to inaccuracies inthe diagnosis. Objective methods for measuring the forces applied on the teeth during swallowing would provide greater diagnostic reliability for speech-language pathologists and orthodontists. This study aims to develop and test a system to measure the forces experienced by a tooth during rest and swallowing. Twenty-eight subjects (10 men and 18 women), aged between 19 and 31 years (mean 23.2) were selected toparticipate in this study after inclusion and exclusion criteria have been applied. Participants underwent clinical assessment of habitual position of the tongue and lips, occlusal pattern and swallowing. Then, measurement of the forces experienced by the upper right central incisor tooth due to the action of upper lip and tongue were made.For that, Flexiforce resistive sensors were fixed on the labial and lingual surfaces of the tooth. The sensors were connected to an amplifier circuit and a data acquisition board for processing and transmitting information to a computer. Data was displayed on a program developed specifically for this study. Results showed that, at rest, the force experienced by the tooth with the tongues action was 0.00±0.00 N and with the lips action was 0.02±0.02 N and the difference between them was significant. Duringswallowing, these values were 0.31±0.38 N and 0.15±0.14 N respectively, without significant difference. The contact time of the tongue and the sensor during swallowing was also analyzed and results showed that it was 1.05 s for directed swallowing and 0.80 s for spontaneous one, without significant difference between them. Theconclusion was that the distribution of forces exerted by the upper lip and tongue on the upper central incisor presents varying pattern, even in individuals with normal occlusion. However, at rest, lip exerts a greater force than tongue and during swallowing, the tongue applies the greater force on the tooth. This system represents an advance because allows objective measurement of rest and swallowing, although more research is needed to improve the technique.